Synthesis and Characterization of a Thiocyanate Bridged Dinuclear Cu(II) Complex Containing Macrocyclic Ligand Derived from Pyridine-2, 6-dicarboxaldehyde and 1, 2-bis(2-aminoethoxy) Ethane (Journal of Bangladesh Academy of Sciences, 2012)
The cyclic (2+2) template condensation of pyridine-2,6-dicarboxaldehyde with 1,2-Bis(2- aminoethoxy) ethane using Pb(SCN)2 gave dinuclear lead (II) complex, Pb2L1(SCN)4 where L1 is a tetra-Schiff-base macrocycle. The transmetallation treatment of Pb2L1(SCN)4 with Cu(ClO4)2.6H2O yield the complex, [Cu2L1(SCN)3(ClO4)] which has been characterized by elemental analysis, IR, ESI-MS spectroscopy and X-ray crystallography. On the basis of spectral data, different geometry of Cu2+ has been suggested. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10924 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 89-96, 2012